2011
DOI: 10.1088/2041-8205/737/2/l31
|View full text |Cite
|
Sign up to set email alerts
|

Redshift Evolution of the Galaxy Velocity Dispersion Function

Abstract: We present a study of the evolution of the galaxy Velocity Dispersion Function (VDF) from z = 0 to z = 1.5 using photometric data from the UDS and NMBS COSMOS surveys. The VDF has been measured locally using direct kinematic measurements from the Sloan Digital Sky Survey, but direct studies of the VDF at high redshift are difficult as they require velocity dispersion measurements of many thousands of galaxies. Taylor et al. (2010) demonstrated that dynamical and stellar mass are linearly related when the struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
128
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(153 citation statements)
references
References 48 publications
(57 reference statements)
22
128
3
Order By: Relevance
“…The dynamical masses were estimated based on a virial relation, the effective radius and the velocity dispersion of each galaxy. The derived effective radius and dynamical mass fit within ≤1σ with the size-mass relation presented by Bezanson et al (2011), predicts values close to those derived here for each galaxy. The calculated distance and dynamical mass are 292.6 Mpc and 1.63 × 10 11 M , respectively.…”
Section: Mfgc 04711supporting
confidence: 85%
“…The dynamical masses were estimated based on a virial relation, the effective radius and the velocity dispersion of each galaxy. The derived effective radius and dynamical mass fit within ≤1σ with the size-mass relation presented by Bezanson et al (2011), predicts values close to those derived here for each galaxy. The calculated distance and dynamical mass are 292.6 Mpc and 1.63 × 10 11 M , respectively.…”
Section: Mfgc 04711supporting
confidence: 85%
“…Velocity dispersion is a measurement of orbital energy and gravitational potential depth. There is evidence from both observations and simulations that velocity dispersion may be a more stable quantity than stellar mass (Loeb & Peebles 2003;Franx et al 2008;van Dokkum et al 2010;Bezanson et al 2011;Oser et al 2012). Additionally, velocity dispersion has been proven to be a better predictor than stellar mass of specific SFR and color (Franx et al 2008;Wake et al 2012b), galaxy clustering properties (Wake et al 2012a; but see also Li et al 2013), and SFR (Bezanson et al 2012) over a wide range of redshift.…”
Section: Ordering Galaxies By Inferred Velocity Dispersionmentioning
confidence: 99%
“…This provides a simple way to link descendant and progenitor populations at different redshifts. This technique has already been used to study the evolution of a number of different galaxy properties: UV luminosity and star formation history (Papovich et al 2011), the stellar velocity dispersion function (Bezanson et al 2011), Hα equivalent width (Fumagalli et al 2012), and mass and structural evolution van Dokkum et al 2010;Brammer et al 2011;Patel et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To calculate σ mod consistently, we therefore scaled the stellar mass with the ratio of the model flux to the Sérsic model flux. Bezanson et al (2011) find that the model and the observed velocity dispersion correlate very well in the range 60 km s −1 < σ < 300 km s −1 , for galaxies in the redshift range 0.05 < z < 0.07, and for a few galaxies with redshifts 1 < z < 2.5. The SDSS spectroscopic sample extends to z ∼ 0.5, and therefore contains many more massive galaxies.…”
Section: Lensesmentioning
confidence: 63%
“…The physical region where the velocity dispersion is averaged is therefore different for a sample of galaxies with different sizes and redshifts. To account for this, we followed Bezanson et al (2011) and scaled the observed spectroscopic velocity dispersion to a fixed size of R e /8 using σ spec = σ ap spec (8.0r ap /R e ) 0.066 , with r ap = 1.5 the radius of the SDSS spectroscopic fiber, R e the effective radius in the r-band, and σ ap spec the observed velocity dispersion. This correction is based on the best-fit relation determined using 40 galaxies in the SAURON sample (Cappellari et al 2006).…”
Section: Lensesmentioning
confidence: 99%